ANALISA ACID VALUE PADA PRODUK OLEIC ACID DENGAN METODE TITRIMETRI - Masdania Zurairah; Yuliana Miranda Syafrizal (Jurnal Ilmiah Hospitality, 2022)
Acid Value is an acid value that indicates the amount of fatty acid that has not become an ester in the sample determined by titration. From the eight samples of Oleic Acid that have been analyzed, the average Acid Value is 198.54. It can be concluded that the Oleic sample has met the company standards of PT. X where the Range Acid Value is 197.5 – 199.